2020
DOI: 10.1038/s41467-020-14764-5
|View full text |Cite
|
Sign up to set email alerts
|

Vascular progenitors generated from tankyrase inhibitor-regulated naïve diabetic human iPSC potentiate efficient revascularization of ischemic retina

Abstract: Here, we report that the functionality of vascular progenitors (VP) generated from normal and disease-primed conventional human induced pluripotent stem cells (hiPSC) can be significantly improved by reversion to a tankyrase inhibitor-regulated human naïve epiblastlike pluripotent state. Naïve diabetic vascular progenitors (N-DVP) differentiated from patient-specific naïve diabetic hiPSC (N-DhiPSC) possessed higher vascular functionality, maintained greater genomic stability, harbored decreased lineage-primed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 66 publications
(141 reference statements)
1
36
0
Order By: Relevance
“…c Western blot analysis of primed (P) and TIRN (N) CB-hiPSC (E5C3). TIRN-CB-hiPSC markedly upregulated naïve epiblast-specific DNMT3L whilst maintaining DNMT1 protein expressions following TIRN reversion 109 , 110 . d Infinium CpG methylation heatmaps of genomic Imprinted promoter regions of a panel of primed and TIRN-reverted isogenic hPSC samples revealed that TIRN-hPSC retains normal somatic epigenomic imprint configurations, similar to their isogenic primed states.…”
Section: Human Totipotent-like Stem Cells With Expanded Embryonic Developmental Potential May Be Necessary For Unlocking Efficient Human–mentioning
confidence: 94%
See 4 more Smart Citations
“…c Western blot analysis of primed (P) and TIRN (N) CB-hiPSC (E5C3). TIRN-CB-hiPSC markedly upregulated naïve epiblast-specific DNMT3L whilst maintaining DNMT1 protein expressions following TIRN reversion 109 , 110 . d Infinium CpG methylation heatmaps of genomic Imprinted promoter regions of a panel of primed and TIRN-reverted isogenic hPSC samples revealed that TIRN-hPSC retains normal somatic epigenomic imprint configurations, similar to their isogenic primed states.…”
Section: Human Totipotent-like Stem Cells With Expanded Embryonic Developmental Potential May Be Necessary For Unlocking Efficient Human–mentioning
confidence: 94%
“…5a, b ). Tankyrase/PARP inhibitor regulated naïve hPSC (TIRN-hPSC) possessed multiple naïve epiblast-like ICM characteristics that included MEK-ERK/bFGF signaling independence, activated phosphorylated JAK/STAT3 signaling, distal OCT4 enhancer usage, global DNA CpG hypomethylation, and increased expression of activated beta-catenin 109 , 110 . Importantly, in contrast to other naïve reversion methods 84 , 94 97 , Zimmerlin et al 109 reported that supplementation of the core LIF-2i cocktail with only this tankyrase / PARP inhibitor (XAV939) protected a wide repertoire of genetically independent TIRN-hPSC lines against the erosion of CpG methylated genomic imprinted regions.…”
Section: Human Totipotent-like Stem Cells With Expanded Embryonic Developmental Potential May Be Necessary For Unlocking Efficient Human–mentioning
confidence: 99%
See 3 more Smart Citations